1996
DOI: 10.1161/01.cir.94.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Oral Contraceptives and Hypertension Among Women in the United States

Abstract: Current users of oral contraceptives had a significant, moderately increased risk of hypertension. However, among this group, only 41.5 cases per 10 000 person-years could be attributed to oral contraceptive use. Risk decreased quickly with cessation of oral contraceptives, and past users appeared to have only a slightly increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
1
20

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(184 citation statements)
references
References 19 publications
4
159
1
20
Order By: Relevance
“…75 Absolute risk was small: only 41.5 cases of hypertension/10 000 person-years could be attributed to OC use. The current risk of OC-induced hypertension is likely lower than reported in the earlier literature because oral contraceptives currently in use contain lower doses of ethinyl estradiol (30-35 mcg) than those previously used and there appears to be a correlation between both oestrogen and progestin dose and blood pressure in OC users.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…75 Absolute risk was small: only 41.5 cases of hypertension/10 000 person-years could be attributed to OC use. The current risk of OC-induced hypertension is likely lower than reported in the earlier literature because oral contraceptives currently in use contain lower doses of ethinyl estradiol (30-35 mcg) than those previously used and there appears to be a correlation between both oestrogen and progestin dose and blood pressure in OC users.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Environmental characteristics, including pre-existing pregnancy-induced hypertension, occult renal disease, obesity, middle age (435 years) and duration of COC use, as well as genetic characteristics, such as family history of hypertension, increase susceptibility to COC-induced hypertension. 17,18 Controlled prospective studies have consistently demonstrated a return of BP to pretreatment levels within 3 months of discontinuing COCs. 16,19 In the Health Survey for England, a cross-sectional survey, mean BP was significantly higher among premenopausal women who were current users of oral contraceptives (COCs and progestin-only) than among non-users.…”
Section: Oral Contraceptives and Bpmentioning
confidence: 99%
“…High oestrogen states such as pregnancy and treatment with the oral contraceptive pill are associated with hypertension and sodium and water retention (Chasen Taber et al, 1996;Hall, 1997). However very little is known about the direct eects of oestradiol on salt absorbing epithelia.…”
Section: Introductionmentioning
confidence: 99%